Lingua, stile e metodo nella prassi traduttiva novecentesca della lirica di Luis Cernuda. - GRASSO, IDA (Scripta, 2021)
The study, centered on the twentieth-century translations of Luis Cernuda’s lyric, investigates the Italian reception of the great author of La Realidad y el deseo, in particular focusing on the translation practices that have conveyed its diffusion. The comparison of Quisiera estar solo en el sur (Un río, un amor) in the versions by Bo, Macrì and Tentori Montalto, brings out the presence of a common translator’s model with a high degree of formal awareness. It is a cultured and refined model, whose incidence and duration should not be separated from a further necessary consideration on the peripherality suffered by Spanish literature in Italian culture, compared with the European canon.